2017
DOI: 10.1016/j.commatsci.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Using graphene to simplify the adsorption of methane on shale in MD simulations

Abstract: a b s t r a c tIn this paper, we explored material similarity between graphene and shale for methane (CH 4 ) adsorption in the shale gas recovery simulations. The reasons of choosing graphene to model shale have been clarified. Through theoretical analysis, we obtained the attenuation law of interaction potential between CH 4 and multilayer graphene. It indicates the adsorption energy of CH 4 on monolayer graphene is closest to that on shale. The limiting heat of adsorption of CH 4 on graphene was calculated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 37 publications
(55 reference statements)
0
45
0
2
Order By: Relevance
“…When the adsorption and desorption properties of shale gas are concerned, graphene slit-shaped nanochannel were widely employed as a representation of organic matter nanopore and showed satisfactory results. [25][26][27]29,30 In this study, a multilayer graphene slit was built up to investigate CO 2 /CH 4 binary mixture competitive adsorption characteristics, as shown in Fig. 1.…”
Section: Model Constructionmentioning
confidence: 99%
“…When the adsorption and desorption properties of shale gas are concerned, graphene slit-shaped nanochannel were widely employed as a representation of organic matter nanopore and showed satisfactory results. [25][26][27]29,30 In this study, a multilayer graphene slit was built up to investigate CO 2 /CH 4 binary mixture competitive adsorption characteristics, as shown in Fig. 1.…”
Section: Model Constructionmentioning
confidence: 99%
“…The effects of temperature, pressure, and pore size on the adsorption performance of pure methane and a CO 2 /CH 4 mixture in the slit pore of shale formations were examined. Lin et al used graphene to simplify the organic matter of a shale matrix and found that the adsorption isotherms of CH 4 in a graphene slit follow a monolayer Langmuir equation [29]. Also, by using graphene slit model, Chen et al [30] and Zhang et al [31] studied the effect of pore size on the adsorption performance of methane.…”
Section: Introductionmentioning
confidence: 99%
“…物质的高效率输运和利用是存在于自然界中的重 要现象, 其主要的表现形式就是跨尺度的分形流道输 运, 如肾脏对血液中代谢废物的处理 [1] 、矿物质在叶 脉中的输运与吸收 [2,3] 、氧气在血管中的输运和消耗 [4] 等, 这种常见并具有巨大实用价值的问题已被广泛研 究, 并被应用于页岩气藏开采 [5,6] 、医学微型快速检测 芯片开发 [7] 、化学高效率催化器制造以及交通网络设 计等诸多领域 [8,9] . 在分形流道系统中, 初级流道(如肾 动脉)流体处于层流主导状态, 具有直径大、流速高的 特点, 能够将物质快速运送至目标区域; 随着向下级流 道发展, 流道逐级收窄流速降低, 近末端流道中流体处 于扩散主导状态, 流体携带的溶质能够通过扩散迅速 抵达反应表面, 使得输运物质被充分利用 [10] .…”
Section: 引言unclassified